More Is Less: Global Warming News Values on Fox Compared to Other U.S. Broadcast News Outlets. (March 2016) - Ahern, Lee; Formentin, Melanie
Past research supports the notion that Fox News Channel (FNC) is more dismissive of global warming than other news outlets. In addition, FNC covers the issue much more often. A qualitative–quantitative content analysis indicates that—for the leading U.S. broadcast and cable news networks overall—coverage of global warming relies on traditional news values such as political-elite cues and event magnitude. FNC, however, exhibited a news agenda favoring more coverage of global warming and climate change (relative to the other leading news outlets). Additional analysis indicates that FNC often co-opts the issue as an exemplar of "political correctness" and of the excess of political progressivism. Other networks, conversely, are more likely than FNC to cover the actual causes and impacts of global warming. Findings are situated in the context of gatekeeping theory; implications of observed network differences are discussed.